2020
DOI: 10.1111/cwe.12354
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Imports and Exports on China's PM2.5 Pollution

Abstract: This paper examines the effects of imports and exports on China's PM2.5 pollution using data from 31 provinces during the period 2001–2016. At the aggregate level, our analysis shows that exports have a pollution‐generating effect while imports have a pollution‐shifting effect on provincial PM2.5 pollution. Cross‐sectional analysis reveals that imports and exports exhibit opposite effects on manufacturing and high‐tech industries, but demonstrate the same pollution‐generating effect for the heavy industry sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Gaigné et al (2012) confi rmed that when the intercity and intra-urban distributions of activities were given, a higher population density made cities more environmentally friendly. Similarly, Li et al (2020) also showed a positive relationship between population density and pollution using provincial data during the period 2001-2016 in China. Moreover, Glaeser and Kahn (2010), in the US, found that the areas with the lowest emissions were generally in California and that the areas with the highest emissions were in Texas and Oklahoma.…”
Section: Introductionmentioning
confidence: 81%
“…Gaigné et al (2012) confi rmed that when the intercity and intra-urban distributions of activities were given, a higher population density made cities more environmentally friendly. Similarly, Li et al (2020) also showed a positive relationship between population density and pollution using provincial data during the period 2001-2016 in China. Moreover, Glaeser and Kahn (2010), in the US, found that the areas with the lowest emissions were generally in California and that the areas with the highest emissions were in Texas and Oklahoma.…”
Section: Introductionmentioning
confidence: 81%
“…Energy is the "food" of industry and an important material basis for economic development [1][2]. In the short term, under the constraints of world energy supply and demand and ecological environment, the change of energy structure can not only inhibit economic growth but also promote economic growth [3][4]. Therefore, the correct analysis of the relationship between energy consumption and industrial output has important theoretical and practical significance for the rational use of energy and sustained and stable economic growth.…”
Section: Introductionmentioning
confidence: 99%